Scorpion sting envenomation, Vijayapur, Karnataka, India experience: new observations - Patil, Mallanagouda M.; Lakhkar, Bhavana; Patil, Shankargouda V.; Akki, Aravind S.; Gobbur, Raghavendra H.; Kalyanshettar, Siddarameshwar S. (International Journal of Contemporary Pediatrics, 2016)
Background: Scorpion sting is a very common problem in rural areas of Vijayapur. Financial status of people and non-availability of antivenin are concerns. The present study enumerates risk factors and experience of using drug Prazosin hydrochloride (Prazosin) at higher initial dose (80-90 microgram/kg) in scorpion sting envenomation. Methods: A retrospective study was carried out at Shri BM Patil Medical College Hospital and Research Centre Vijayapur Karnataka during the period of September 2014 to August 2015. Case records of 40 cases of scorpion sting envenomation were reviewed. Risk factors were correlated with outcome. Effect of accidental administration of high dose of Prazosin was studied. Results: Local pain, profuse sweating, vomiting, cold extremities were common presentations. Six patients had myocarditis and one had neurological involvement. One patient was brought dead. Age of patient, time interval between symptoms and treatment, use of steroids and other drugs were main risk factors. High dose Prazosin reduced the time for first response (p= <0.001), total recovery time (p= <0.001), Pediatric Intensive Care Unit stay (p= <0.001) and use of inotropes (P=0.042). Conclusions: High dose Prazosin is useful and safe in severe cases of scorpion sting envenomation in the resource poor settings.